Disparities in police proceedings and court sentencing for females versus males who commit sexual offences in New Zealand. Issue 2 (4th May 2019) - Patterson, Tess; Hobbs, Linda; McKillop, Nadine; Burton, Kelley
ABSTRACT: This study investigated whether there are disparities in the way in which police proceed against females and males who commit sexual offences. We explored whether there are discrepancies in the severity of court sentences handed down to female and male sexual offenders. Using police and sentencing data, we compared the proportion of females and males who proceeded to court action once charged with a sexual offence and, separately, the severity of sentencing handed down to both genders. In terms of police decision-making processes, compared to males, a smaller proportion of females proceeded to "court action" for their offences. Furthermore, the severity of sentences handed down to males was greater than those handed down to females, both generally and when the sexual offence could be directly matched. These findings are discussed in the context of gender differences in how these crimes are processed and implications for justice, intervention, and community safety.